2017
DOI: 10.1016/j.cortex.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal reorganization of the reading network in adult dyslexia

Abstract: Developmental dyslexia is characterized by impairments in reading fluency and spelling that persist into adulthood. Here, we hypothesized that high-achieving adult dyslexics (i.e., university students with a history of dyslexia) manage to cope with these deficits by relying to a greater extent on morphological information than do non-impaired adult readers. We used magnetoencephalography (MEG) in a primed lexical decision task, in which we contrasted orthographic, morphological and semantic processing. Behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 80 publications
6
30
3
Order By: Relevance
“…The delayed activation of the phonological code in adults with dyslexia reported here may reflect a general weakness of the reading system, which itself, was caused by inadequately developed phonological representations during oral language acquisition. As previously argued in the literature (Torppa et al 2010), a poorly developed oral language would entail poorly developed orthographic code, diminished synchronization between the phonological and orthographic codes (Breznitz and Misra 2003), as well as less efficient connections with the semantic code (Gentaz et al 2015).…”
Section: Phonological Skills In Adults With Dyslexiamentioning
confidence: 72%
“…The delayed activation of the phonological code in adults with dyslexia reported here may reflect a general weakness of the reading system, which itself, was caused by inadequately developed phonological representations during oral language acquisition. As previously argued in the literature (Torppa et al 2010), a poorly developed oral language would entail poorly developed orthographic code, diminished synchronization between the phonological and orthographic codes (Breznitz and Misra 2003), as well as less efficient connections with the semantic code (Gentaz et al 2015).…”
Section: Phonological Skills In Adults With Dyslexiamentioning
confidence: 72%
“…Our results are in agreement with these past findings, which conclude that individuals with dyslexia have a deficit in MA relative to typical readers of the same age. Yet, previous studies have also demonstrated that individuals with dyslexia perform as well as or better than younger, reading age-matched controls on MA tasks, which suggests that the MA deficit observed in dyslexics is not causal of their word reading deficit and is potentially a consequence of their poor reading experience or poor PA skills (Cavalli et al, 2017; Martin et al, 2014; Robertson et al, 2013; Tsesmeli & Seymour, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Based on this initial evidence, it is important for future research (ideally with larger sample sizes that would allow regression-based analytical approaches) to investigate within a single study the percentage of reading behavior variance explained by each of these reading constituents in readers with and without dyslexia. It will be especially important to examine whether or not dyslexic readers use semantic and/or orthographic skills to compensate for other reading difficulties (e.g., Cavalli et al, 2017 ) and to what extent they do so. Another important goal for future research would be to investigate regional hypoactivations and functional connectivity in right-lateralized regions that may play a specific role in some of the major components of reading examined here, in line with accounts that highlight the role of right-hemisphere compensatory mechanisms in dyslexia.…”
Section: Discussionmentioning
confidence: 99%